Unmanned Aerial Systems for Indoor Inspection in Industrial Sites: System Architecture, Sensors, and Simulation Techniques - Santos, Matheus M.; Pinheiro, Pedro M.; Maurell, Igor; Soares, Luciane; Nam-Jr, Je; Nunes, Pedro E.; Evangelista, Eduardo; Maurente, Vinicius V.; Costa, Cedenir B.; Borges, Eduardo N.; Gonçalves, Eder M. N.; Pias, Marcelo; et al. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Corrosion is a major problem in industrial facilities and marine vessels, leading to structural damage, safety risks, and expensive maintenance. Using UAVs for corrosion inspection offers several benefits, including improved operator safety, increased efficiency, and enhanced risk assessment. High-resolution cameras and specialized sensors allow for quick and accurate assessments of hard-to-reach areas, eliminating the need for manual inspections. Additionally, UAVs can capture visual data, including images of irregular surfaces and ultrasonic thickness measurements, which are crucial for comprehensive analysis. This paper discusses a new solution for efficient corrosion inspection and management using Unmanned Aerial Vehicles (UAVs) equipped with advanced sensors and autonomous flight capabilities. It explores potential methodologies and techniques for visual inspection, localization, and navigation, aiming to implement, simulate, and construct an effective inspection system.